2009
DOI: 10.1002/mds.22678
|View full text |Cite
|
Sign up to set email alerts
|

Association of DRD3 and GRIN2B with impulse control and related behaviors in Parkinson's disease

Abstract: We aimed to assess whether allelic variants of dopamine receptor, glutamate receptor, and serotonin transporter genes are associated with the appearance of impulse control and related behaviors (ICRB) in Parkinson's disease (PD) with dopamine replacement therapy (DRT). We surveyed ICRB in consecutive Korean patients with PD who were treated with stable DRT using modified Minnesota Impulsive Disorders Interview over a period of 4 months. In the 404 patients who completed the interview and the 559 Korean healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 35 publications
4
114
1
4
Order By: Relevance
“…Medication practices, cost burdens, and health insurance have been suggested as potential factors with influencing the different prevalences (Fan et al., 2009). Genetic variants of serotonin receptors and polymorphisms for the dopaminergic, serotonergic, glutamate, and opioidergic systems have been related to the development of ICB in patients with PD (Comings & Blum, 2000; Ibanez, Blanco, Perez de Castro, Fernandez‐Piqueras, & Saiz‐Ruiz, 2003; Kraemmer et al., 2016; Le Foll, Gallo, Le Strat, Lu, & Gorwood, 2009; Lee, Jeon, Kim, & Park, 2012; Lee et al., 2009; Zainal Abidin et al., 2015). Thus, genetic variations in receptors, transporters, or enzymes of the catecholaminergic, serotonergic, glutamatergic, and opioid neurotransmission systems are potentially associated with ICD in PD (Jimenez‐Urbieta et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Medication practices, cost burdens, and health insurance have been suggested as potential factors with influencing the different prevalences (Fan et al., 2009). Genetic variants of serotonin receptors and polymorphisms for the dopaminergic, serotonergic, glutamate, and opioidergic systems have been related to the development of ICB in patients with PD (Comings & Blum, 2000; Ibanez, Blanco, Perez de Castro, Fernandez‐Piqueras, & Saiz‐Ruiz, 2003; Kraemmer et al., 2016; Le Foll, Gallo, Le Strat, Lu, & Gorwood, 2009; Lee, Jeon, Kim, & Park, 2012; Lee et al., 2009; Zainal Abidin et al., 2015). Thus, genetic variations in receptors, transporters, or enzymes of the catecholaminergic, serotonergic, glutamatergic, and opioid neurotransmission systems are potentially associated with ICD in PD (Jimenez‐Urbieta et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine D3 receptors, predominantly distributed within the limbic system [6,16] regulate dopamine release within the mesocorticolimbic pathway [17]. The association of the DRD3 p.S9G polymorphism in the development of ICDs in PD may be explained by this form of the receptor demonstrating a reduced binding affinity to dopamine [35], which may result in inappropriate dopamine-mediated stimulation of the mesocorticolimbic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…No such association has been found for other variants of dopamine receptors [35]. Eisenegger et al [36] has also demonstrated a further possible genetic component that may influence the development of compulsive behaviours in patients with PD: administration of L-DOPA was found to result in significantly greater gambling tendencies in healthy males with the dopamine receptor 4/7 polymorphism genotype compared to the 4/4 polymorphism.…”
Section: Genetic Influence On Development Of Impulsive Behaviour (Tabmentioning
confidence: 99%
“…Moreover, DRD2 rs1799732 Ins/Ins genotype was associated with gastrointestinal AEs (nausea and vomiting) after L-Dopa therapy [36]. Association of DRD3 variants with drug outcome in PD was shown in at least five pharmacogenetic studies [23,[36][37][38][39]. DRD3 rs6280 AA genotype (Ser/Ser) was shown to be associated with increased risk for developing ICDs and gastrointestinal AE [36,37].…”
Section: Genetic Factors and Treatment Response In Pdmentioning
confidence: 99%